Rancang Bangun Prototype Alat Pemilah Limbah Logam Dan Plastik Otomatis Berbasis Arduino Uno - Sahfira Isnaini Lubis; Ummul Khair; Imran Lubis (ALGORITMA : JURNAL ILMU KOMPUTER DAN INFORMATIKA, 2021)
Along with the rapid development of technology, where the role of humans has been replaced with many machines or robots in doing a job. In everyday life humans usually always produce waste. Waste is defined as material that is wasted or discarded due to human activities that do not or do not yet have economic value and positive value can even have a negative economic value. the more system requirements within the company's industrial environment are increasingly being used to make it easier and to shorten the time for each activity in the company's industry. The current system is still manual, especially in the process of sorting waste items where there are still errors such as frequent mixing of metal and plastic waste items and employees automatically sort out the waste. Where conditions like that are not very good and spend a lot of time. The aim of this research is to make a waste sorting tool based on metal and plastic materials, this tool uses Arduino as a microcontroller, proximity sensor as a reader of metal waste and uses a servo motor as a separator, and conveyor as a driving force for yield. this research is expected to be able to help users or company owners to simplify the sorting process. Keywords: Arduino, Proximity Sensor, Servo Motor, Conveyor